Welsh Speakers’ Dementia Care - Alzheimer's Society Cymru; Welsh Language Commissioner (Welsh Government, 2018)
The Welsh Language Commissioner and Alzheimer’s Society Cymru have collaborated on a project focussing on the Welsh language and dementia. The research company Wavehill was commissioned to undertake a study of the care and support services delivered to Welsh speakers with dementia. This qualitative research involved consultation with senior officers from local authorities and health boards; academics in the field; care and support providers; and people living with dementia. The purpose of the study was to investigate the main factors and themes influencing the provision, or lack of provision, of Welsh medium dementia health and support services, and learn about the experience of Welsh speakers with dementia of that provision. A round-table event was held with experts in the field to discuss the findings of the research and offer possible policy solutions in response to the difficulties identified. This document summarises the findings of the project. Firstly, it outlines the nature of dementia and highlights the relevant language considerations. It then discusses the policy and legislative developments that are relevant to the field. We then present the findings of our research and the experiences of those living with dementia of the Welsh medium care available to them. Finally, it highlights the difficulties identified and the policy solutions which could, if adopted, make a positive difference to the provision for Welsh speakers.
Number of pages: 61

Welsh Speakers’ Experiences of Health and Social Care Services - IAITH: Welsh Centre for Language Planning for the Department for Health, Social Services and Children (Welsh Government and the Care Council for Wales, 2012)
Nombre de pages: 73

Welsh in the health service: The scope, nature and adequacy of Welsh language provision in the National Health Service in Wales. Consumer Council Wales. - Misell, Andrew (2000)
The Welsh Consumer Council set about defining the consumer interest in language in its 1996 report, Welsh as a Consumer Issue. That report emphasised how and why the opportunities for using the Welsh language be considered from the view of the consumer. In general, service providers are well equipped to look after their own interests – the consumer by comparison is often weak. It is this theme that is picked up in this report – Welsh in the Health Service: The Scope, Nature and Adequacy of Welsh Language Provision in the National Health Service in Wales. While the report recognises that, in many instances, Welsh language service provision is about providing equal opportunities and ensuring a high quality, consumer sensitive service, it also identifies groups for whom service provision in the first language is a clinical necessity. The report concludes that in the case of Welsh-speaking patients, there are instances when they cannot be treated effectively except in their first language, or in both their languages. This is especially true in the case of those receiving speech and language therapy, and for the following key groups: - people with mental health problems. - people with learning disabilities and other special needs. - older people, and - young children. The report contains many recommendations and calls for a fundamental change of approach on the part of the NHS in Wales.
Nombres de pages: 85

Social exclusion among official language minority older adults: A rapid review of the literature in Canada, Finland and Wales - Nyqvist, Fredica; Häkkinen, Emilia; Renaud, Alexandre; Bouchard, Louise; Prys, Cynog (Journal of Cross-Cultural Gerontology, 2021)
It has been suggested that older adults from minority linguistic and ethnic communities face higher risks of being socially excluded. The aim of this review was, therefore, to explore and review social exclusion studies conducted among official language minority older adults in three countries, namely Canada, Finland and Wales. A rapid review approach was used to review scientific literature in line with six social exclusion domains. The literature searches were made in Finnish, Swedish, English, French and Welsh and were restricted to research published within the timeline of 2001 – September 2019 and yielded 42 articles. The included studies were categorized into three different domains: socioeconomic influences, social participation and societal conditions. Converging and diverging patterns of social exclusion in old age were identified between the linguistic minorities. Linguistic barriers regarding access to health care and receiving health information were common across the three linguistic contexts, whereas exclusion from social participation was noticed amongst the linguistic minorities in Canada and Wales. Some connections between belonging to a linguistic minority and being exposed to a lower socioeconomic status and higher poverty risk were made, however, these findings were not robust across all three countries. The findings indicated that experiences of exclusion could be considered fairly common among linguistic minority older adults. We conclude that the research evidence presented in the review sheds light on issues of social inequality in old age between linguistic majorities and minorities, thus identifying important aspects of social exclusion to guide future research as well as policy and practice.